Pemanfaatan Bahan Sederhana Menjadi Alat Peraga Keranjang Faktor untuk Meningkatkan Hasil Belajar Matematika Materi FPB dan KPK pada Siswa Kelas V SDN 10 Mataram - Irni, Hj (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
The background study of this research was result of students’ mathematic achievement at fifth grade of SDN 10 Mataram on FPB and KPK material was low. It caused by teachers didn’t use props which suitable in learning process. To solve problem above, it was conducted action with using props cart factor to improve result of students’ mathematic achievement at fifth grade students of SDN 10 Mataram on FPB and KPK materials. Stage of this research consisted of planning, acting, observing, evaluating and reflecting. Subject of this research was all of fifth grade students of SDN 10 Mataram was 47 students, consisted of 21 female students and 26 male students. Data of this research was result of students’ learning achievement and teachers’ activities and students’ activities. Result of students’ learning was gotten with giving test and data of teachers’ activities and students’ activities was gotten through observation sheet. Score of students’ activities was 20,66 and teachers’ activities was 22,68 with very good category. And mean score of students was 79,02. That score showed that there is improved from previous year got score 66,54. Beside that classical completeness was improved from academic year 2013/2014 with percentage of completeness was 32,61% become 85,11% in acedemic year 2014/2015. Conclusion of using prop cart factor was prop cart factor could improve result of learning achievement on FPB and KPK materials at fifth grade students of SDN 10 Mataram.